The Wiley handbook of social studies research - Manfra, Meghan McGlinn; Bolick, Cheryl Mason (UK : WILEY Blackwell, 2017)
The Wiley Handbook of Social Studies Research is a wide-ranging resource on the current state of social studies education. This timely work not only reflects on the many recent developments in the field, but also explores emerging trends.
Includes bibliographical references and index.
Keywords: Social sciences -- Handbooks, manuals, etc. -- Research